Mediatilistika v Ukraïni: problemy ta perspektivy rozvytku - Mamič, Miroslava B. (Stylistyka, 2020)
The article is devoted to the problem of modern journalism knowledge that is developing a media stylistic direction. The basie problems that need processing were introduced, three main approaches to the analysis of the journalism language were determined: normative and stylistic, communicative, pragmatic, communicative and stylistic. Attention was focused on the need to differentiate media stile oťadvertising text, media style of newspaper and magazíne texts, Web address texts, radio and television, as well as linguistic and structural aspects media style. Marked the importance of studies aimed at updating process of oral speech, inleractivity in the language of modem media.